Engineering characteristics of dune sand-fine marble waste mixtures - Qureshi, Mohsin U.; Mahmood, Zafar; Farooq, Qazi U.; Qureshi, Qadir B.I.L.; Al-Handasi, Hajar; Chang, Ilhan (Geomechanics and Engineering, 2022)
Dune sands are poorly graded collapsible soils lacking fines. This experimental study explored the technical feasibility of sustainable invigoration of fine waste materials to improve the geotechnical properties of dune sand. The fine waste considered in this study is fine marble waste. The fine waste powder was mixed with dune sand at different contents (5, 10,15, 20, 25, 50%), where the gradation, void ratio, compaction, and shear strength characteristics were assessed for each fine marble waste-dune sand blend. The geotechnical properties of the dune sand-fine marble waste mix delineated in this study reveal the enhancement in compaction and gradation characteristics of dune sand. According to the results, the binary mixture of dune sand with 20% of fine marble waste gives the highest maximum dry density and results in shear strength improvement. In addition, a numerical study is conducted for the practical application of the binary mix in the field and tested for an isolated shallow foundation. The elemental analysis of the fine marble waste confirms that the material is non-contaminated and can be employed for engineering applications. Furthermore, the numerical study elucidated that the shallow surface replacement of the site with the dune sand mixed with 20% fine marble waste gives optimal performance in terms of stress generation and settlement behavior of an isolated footing. For a sustainable mechanical performance of the fine marble waste mixed sand, an optimum dose of 20% fine marble waste is recommended, and some correlations are proposed. Thus, for improving dune sand’s geotechnical characteristics, the addition of fine marble waste to the dune sand is an environment-friendly solution.
Keywords: Collapsible soil; Dunes sands; Engineering characteristics; Fine marble wastes; Fine wastes; Geotechnical properties; Shallow foundations; Shears strength; Voids ratio; Waste mixtures; dune sand; fine marble waste; numerical modelling; shallow foundation; shear strength